Characterization of the development dynamics within the linear growth bamboo leaf. Issue 3 (10th February 2021) - Gao, Zhipeng; Guo, Lin; Chen, Ming; Yu, Fen; Wei, Qiang
Abstract: The leaf is the main photosynthetic organ in plants, such as bamboo. Leaves from bamboo are used as a food additive. However, according to our investigation, to date there have been no reports concerning the leaf development of bamboo. By measuring over 7500 parenchymal cells, we discovered that the linear leaf growth of Pseudosasa japonica could be divided into three growth sections. The first one is a roughly 1‐cm long division zone (DZ), containing about 1580 cells, located at the bottom of the leaf; the second one is an about 3‐cm long elongation zone (EZ), with ~1905 cells, located above the DZ; and the last is a mature zone (MZ) in which cell elongation is completed. The cell production rate of the DZ was 25.33–35.81 cells per hour, with an average of 29.73; and the cell division rate was ~0.45 cells per cell every 24 h. PacBio and Illumina transcriptome sequencing found 21 933 unigenes expressed in these zones. Further analysis revealed a dynamic transcriptome, with transcripts for cell division in the DZ changing to transcripts for cell elongation, photosynthetic development, secondary metabolism, stress resistance, and nutrition transport toward the leaf distal. Those transcriptome transformations correlated well with the changes of relative water content, biomass accumulation, and cellulose crystal degree and were supported by quantitative polymerase chain reaction data. These results revealed a developmental gradient of the bamboo linear growth leaf, which offers a foundation to elucidate and engineer leaf development in bamboo, an economically valuable plant.